2010
DOI: 10.1016/j.biocon.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Host taxon-derived Sarcoptes mite in European wild animals revealed by microsatellite markers

Abstract: Ten markers specific to Sarcoptes mites were used in applying microsatellite genotyping to individual Sarcoptes mites collected in three European countries from 15 wild mammal populations belonging to 10 host species. The results showed that geographical separation had real biological significance for the definition of mite sub-populations, and that the degree of genetic exchange occurring between mites from different localities was apparently related to the geographical distance between locations. Wild hostde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(123 citation statements)
references
References 56 publications
11
110
0
Order By: Relevance
“…Morphological variation between the strains is small or absent, and ITS-2 also shows no host-related variation (Alasaad et al 2012 ). However, there is some evidence of host-related population genetic differentiation in microsatellites (Rasero et al 2010 ) as well as physiological differences among scabies mites from different hosts. Experimental attempts to transfer scabies from dogs to mice, rats, guinea pigs, pigs, cattle, cats, goats and sheep were unsuccessful, although most of these hosts are parasitised naturally by S. scabiei .…”
Section: Mites On and In Mammalsmentioning
confidence: 96%
See 1 more Smart Citation
“…Morphological variation between the strains is small or absent, and ITS-2 also shows no host-related variation (Alasaad et al 2012 ). However, there is some evidence of host-related population genetic differentiation in microsatellites (Rasero et al 2010 ) as well as physiological differences among scabies mites from different hosts. Experimental attempts to transfer scabies from dogs to mice, rats, guinea pigs, pigs, cattle, cats, goats and sheep were unsuccessful, although most of these hosts are parasitised naturally by S. scabiei .…”
Section: Mites On and In Mammalsmentioning
confidence: 96%
“…Examples of the fi rst situation include the green conure with at least 25 species of feather mites (Pérez 1997 ) and the scarab Copris hispanus with 19 species of acarine symbionts (Hunter and Rosario 1988 ). Examples of multi-host mites include: the water mite Protzia eximia on 25 species of insect hosts, including Simuliidae, Chironomidae and various Trichoptera (Ullrich 1976 ); Sarcoptes scabiei complex on 40 species belonging to seven orders of mammals (Arlian 1989b ; but see Rasero et al 2010 for evidence of host-associated differentiation of S. scabiei ); and Pyemotes ventricosus on 139 species of insects in six orders (Eickwort 1983 ). Any coevolution in these cases would have to be very diffuse indeed.…”
Section: Coevolution By Mutual Adaptationmentioning
confidence: 99%
“…Changes in antigen conformation may lead to variable epitope exposure to antibodies and lower test sensitivity (Casais et al 2013). Wild boar can be repeatedly infested by mites from different subpopulations (Rasero et al 2010), and each mite strain produces some unique antigen (Arlian et al 1996), which may involve differences in the circulating antibodies. Furthermore, repeated freeze-thaw cycles (as occurred for the used samples from captured wild boar) may cause a decrease in optical density values (Boadella and Gortázar 2011), a factor possibly contributing to the doubtful or negative results in a few wild boars expected to be antibody positive.…”
Section: Elisa Sarcoptes-elisa 2001mentioning
confidence: 99%
“…Rd18 had both Group 1 and Group 2 mites. Rasero et al (2010) demonstrated the utility of analyzing microsatellite loci to differentiate between carnivore-associated Sarcoptes mite populations in an analysis between three geographically separated carnivore hosts from Italy and Spain. Using these microsatellite loci, the results in the present study strongly suggest that the difference of host species did not disrupt the gene flow of Sarcoptes mites between domestic/companion dogs and raccoon dogs, which would be caused by the transmission of sarcoptic mange between raccoon dogs and domestic/companion dogs, at least around the Gifu area of Japan.…”
Section: Figmentioning
confidence: 99%